1. The problem statement, all variables and given/known data Use implicit diff to find partial x and partial y if x² + y² + z² = 3xyz 3. The attempt at a solution firstly with partial x... 2x + 2z(∂z/∂x) = 3yz + 3xy(∂z/dx) 2x - 3yz = 3xy(∂z/dx) - 2z(∂z/∂x) 2x - 3yz = (3xy - 2z)(∂z/dx) (2x - 3yz)/(3xy - 2z) = (∂z/dx) yet in the solutions, they have moved all the (∂z/dx) terms to the left hand side thus giving (∂z/dx) = (3yz - 2x)/(2z - 3xy) Quite obviously this is not the same as my answer. My question is why should the two answers differ? MUST you take all (∂z/dx) terms to the left hand side as some sort of convention?